Prioritizing security cooperation with highly capable U.S. allies framing army-to-army partnerships - O'Mahony, Angela; Thaler, David E.; Grill, Beth; Moroney, Jennifer D. P. 1973-; Campbell, Jason H.; Tecott Metz, Rachel; Adgie, Mary Kate (RAND, 2022)
"The U.S. strategic security environment has undergone a shift during the past decade: The regional focus on countering violent extremist organizations has given way to long-term global competition against near-peer adversaries Russia and China. Security cooperation, especially with our closest, most-capable (highly capable) allies, is emphasized as a high-priority tool for pursuing an extensive array of overlapping national interests. The United States and its allies recognize that, in a time of increasing requirements and limited resources, they must work in coalitions and engage regional stakeholders by bringing different strengths and perspectives to combined efforts. However, recent operations and efforts suggest that more can be done to create and sustain the mechanisms that increase the effectiveness of joint activities. In this report, researchers present recommendations for enabling the U.S. Army to better prioritize and coordinate its security cooperation activities with its allies for coalition operations and engagements in third countries, allowing it to meet its assigned objectives and strengthen combined capabilities to compete strategically and counter common threats around the world. Researchers adopted a mixed-method approach focused on Australia and the United Kingdom that combined a literature review of findings on security cooperation uses and effectiveness; a database analysis of recent U.S. security cooperation; a historical analysis of secondary sources documenting recent overseas contingency operations; and interviews with key stakeholders."--
Keywords: Bündnis; Sicherheitspolitik; USA; United States / Military relations; United States / Army; National security / United States; United States / Military policy; États-Unis / Army; États-Unis / Relations militaires